Features, origin and distribution of microbial dolomite reservoirs: A case study of 4th Member of Sinian Dengying Formation in Sichuan Basin, SW China - CHEN, Yana; SHEN, Anjiang; PAN, Liyin; ZHANG, Jie; WANG, Xiaofang (Petroleum exploration and development, 2017)
Based on the drilling cores and slice observations, single well data and geochemical analysis, this paper analyzed features, origin and distribution of the 4th Member reservoirs of Sinian Dengying Formation (Z2dn4) in the Sichuan Basin. It is demonstrated that the main reservoir is a set of microbial dolomites. The discovery of spherical dolomite has revealed that the dolomitization was related to the microbial action, belonging to the early protodolomite of low-temperature precipitation; the primary matrix pores and the penecontemporaneous eroded pores constituted the subject of the reservoir space, which was not due to the interlayer karst process related to the Tongwan Movement and burial-hydrothermal dissolutional process. The microbial mound-shoal complex and penecontemporaneous dissolution mainly control the development and distribution of the scaled reservoirs in Z2dn4. The microbial dolomite reservoir surrounding the intracratonic rift had a large thickness, good continuity and high quality, and was an important target of the survey.